Case report of a neonate with high viral SARSCoV-2 loads and long-term virus shedding - Monique A.L.J. Slaats; Maud Versteylen; Karin B. Gast; Bas B. Oude Munnink; Suzan D. Pas; Robbert G. Bentvelsen; Ron van Beek (Elsevier, 2020)
Background: SARS-CoV-2 has spread globally. Currently, literature of SARS-CoV-2 in neonates is scarce. We present a case of a neonate with a high viral load and prolonged virus shedding. Methods: Epidemiology, clinical characteristics, treatment, laboratory data and follow-up information and the treatment of a neonate with COVID-19 were recorded. Results: A 7-day-old boy was admitted to the hospital with fever, lethargy and apnoea. He was found SARS-CoV-2 RNA positive with an exceptionally high viral load in nasopharyngeal swab and stool. The father and two maternity nurses at home had detectable SARS-CoV-2 RNA as well. Sequencing showed all strains belonged to the same cluster. The father was asymptomatic and the maternity nurses developed symptoms after visiting. In the mother, no SARS-CoV-2 RNA could be found. Six days after admission, the neonate was discharged after clinical improvement with oral antibiotics because of a possible pyelonephritis. Monitoring the course of this infection showed that SARS-CoV-2 RNA was detectable in the nasopharynx until day 19 and in stool until day 42 after symptom onset. Conclusions: This case shows that neonates can have a high viral load of SARS-CoV-2 and can shed the virus for over one month in stool. Despite the high viral load in the neonate, the mother and a sibling did not get infected.